2014
DOI: 10.1038/jp.2014.47
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lactation stage, gestational age and mode of delivery on breast milk microbiota

Abstract: Lactation stage, gestational age and delivery mode all influence the composition of several bacteria inhabiting BM: Bifidobacterium, Lactobacillus, Staphylococcus, Streptococcus and Enterococcus spp., and, consequently, may affect the infant's early intestinal colonization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
233
0
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(249 citation statements)
references
References 39 publications
5
233
0
11
Order By: Relevance
“…[95][96][97] Intriguingly, in addition to skin-associated (Staphylococcus) and oral-associated (Streptococcus) taxa, the milk microbiome includes anaerobic bacteria most commonly associated with the gut such as Bifidobacteria and Enterococcus. 94 The origin of these bacteria has yet to be fully elucidated, but evidence suggests that these bacteria may be translocated from the maternal gut via enteromammary trafficking, a pathway in which bacteria in the gut lumen are engulfed by leukocytes through the process of antigen sampling and translocated intracellularly to the mammary glands via systemic circulation (For a review see ref 98 ). In support of this hypothesized pathway, a study of mothers given oral Lactobacillus probiotics for the treatment of mastitis showed that the Lactobacillus strains were detected in the breast milk of 6 out of 10 mothers after oral probiotic administration.…”
Section: Impact Of Maternal Nutrition During Breastfeedingmentioning
confidence: 99%
See 1 more Smart Citation
“…[95][96][97] Intriguingly, in addition to skin-associated (Staphylococcus) and oral-associated (Streptococcus) taxa, the milk microbiome includes anaerobic bacteria most commonly associated with the gut such as Bifidobacteria and Enterococcus. 94 The origin of these bacteria has yet to be fully elucidated, but evidence suggests that these bacteria may be translocated from the maternal gut via enteromammary trafficking, a pathway in which bacteria in the gut lumen are engulfed by leukocytes through the process of antigen sampling and translocated intracellularly to the mammary glands via systemic circulation (For a review see ref 98 ). In support of this hypothesized pathway, a study of mothers given oral Lactobacillus probiotics for the treatment of mastitis showed that the Lactobacillus strains were detected in the breast milk of 6 out of 10 mothers after oral probiotic administration.…”
Section: Impact Of Maternal Nutrition During Breastfeedingmentioning
confidence: 99%
“…Once thought to be sterile, it is now wellestablished that human milk contains a distinct microbiome consisting of diverse species. 93,94 These bacteria seed the gastrointestinal tract of the breastfeeding infant, likely contributing to the significant shifts in microbiome composition associated with breastfeeding. [95][96][97] Intriguingly, in addition to skin-associated (Staphylococcus) and oral-associated (Streptococcus) taxa, the milk microbiome includes anaerobic bacteria most commonly associated with the gut such as Bifidobacteria and Enterococcus.…”
Section: Impact Of Maternal Nutrition During Breastfeedingmentioning
confidence: 99%
“…One may argue that bifidobacteria, even when they decrease in relative abundance following weaning, persist following their initial transfer to the infant gut. The particular route(s) used for such a transfer is still unknown, although it has been speculated that transfer is facilitated by a human milk route (42,43) and/or by contamination of fecal and vaginal samples in the partum canal (44). Very recently, the possibility of fetal colonization of the infant gut through the placenta has been put forward (45).…”
Section: Resultsmentioning
confidence: 99%
“…High levels of maternal salivary mutans streptococci have been also related to an increase in the risk of ECC [39]. Another issue that has been reported refers to the differences in the breast milk microbiota according to the mode of delivery, which will have an impact on early oral colonization of breastfed children [35, 40-42]. This large set of factors could explain why the association between mode of delivery and oral colonization by caries-related microorganisms and by protective microorganism against caries is not consistent across studies.…”
Section: Discussionmentioning
confidence: 99%